Pengaruh Meronce Manik-Manik Terhadap Kemampuan Kognitif Anak Usia 7-8 Tahun - Sunarto Sunarto (Universitas Trunojoyo Madura, 2016)
Cognitive ability is part of the process that occurs internally within the central nervous system at the time people are thinking, and cognitive is one of progress that must progress in every level. This study takes the issue of how Meronce beads affect the cognitive abilities of children aged 7-8 years. The subjects of this research are 1st grade SDN Bulukidul Balong Ponorogo. This research is a type of experimental research. The result of this research shows that the application of meronce pattern of geometric beads gives significant result to the cognitive ability of the child, as evidenced by the increase of children's cognitive ability score before and after the application of meronce pattern of geometric beads. Changes in cognitive abilities of children is shown by the increased ability of children in terms of grouping and sorting in accordance with predetermined patterns. Initially the child still can not know the forms of geometry, after the child is invited to play meronce patterns of geometry beads, the child can know the forms of geometry and can group and sort in accordance with predetermined patterns.